2015
DOI: 10.1016/j.scitotenv.2014.09.051
|View full text |Cite
|
Sign up to set email alerts
|

Long term effects of prenatal and postnatal airborne PAH exposures on ventilatory lung function of non-asthmatic preadolescent children. Prospective birth cohort study in Krakow

Abstract: The main goal of the study was to test the hypothesis that prenatal and postnatal exposure to polycyclic aromatic hydrocarbons (PAH) is associated with depressed lung function in non-asthmatic children. The study sample comprises 195 non-asthmatic children of non-smoking mothers, among whom the prenatal PAH exposure was assessed by personal air monitoring in pregnancy. At the age of 3, residential air monitoring was carried out to evaluate the residential PAH exposure indoors and outdoors. At the age of 5 to 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
1
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 44 publications
(54 reference statements)
2
32
1
3
Order By: Relevance
“…Jedrychowski et al evaluated 195 children without asthma of non-smoking mothers. The highest levels of PAHs during pregnancy were associated with a reduced FEV 1 and a reduced FEV 25–75 40. The same authors have reported that the number of wheezing days during the first 2 years of life was positively associated with the prenatal level of PAH-adducts (incidence rate ratio [IRR] =1.69; 95% CI: 1.52–2.88) 41.…”
Section: Methodsmentioning
confidence: 95%
“…Jedrychowski et al evaluated 195 children without asthma of non-smoking mothers. The highest levels of PAHs during pregnancy were associated with a reduced FEV 1 and a reduced FEV 25–75 40. The same authors have reported that the number of wheezing days during the first 2 years of life was positively associated with the prenatal level of PAH-adducts (incidence rate ratio [IRR] =1.69; 95% CI: 1.52–2.88) 41.…”
Section: Methodsmentioning
confidence: 95%
“…In fact, height charts of these children have been found to be in the lower percentiles. The effect of perinatal exposure to PAHs has also been studied, revealing compromised lung function in otherwise-healthy children 37 . Various studies have shown that indoor air pollution is associated with a 38% increased risk of low birth weight and an alarming 51% increased risk of stillbirths 38 .…”
Section: Effects Of Household Air Pollutionmentioning
confidence: 99%
“…Retention of a subject cohort to study over several years is difficult, and results may be confounded, particularly if families move to a region with different exposures. 79 However, despite the methodologic problems, there is strong evidence from at least 9 selected and well-controlled longitudinal studies (reviewed in Table 2, [71][72][73][74][75][76][77][78][79], that children exposed to greater concentrations of complex air pollutants are at risk for not achieving their optimal lung development by the time they attain adulthood.…”
Section: Traffic-related Pollutants and Lung Functionmentioning
confidence: 99%